Teledentistry protocol for the elderly in the context of the COVID-19 pandemic through a web platform/mobile app: approach from the general dentist - Cristina Sanzana-Luengo; Leonardo Díaz; Liliann Abarza; Eloy Alvarado; Víctor Beltrán (Universidad de Concepción., 2022)
Objective: To generate teledentistry protocols for urgent and priority dental care for the elderly population through a technological web platform and mobile application in the context of the COVID-19 pandemic. Material and Methods: Teledentistry protocols were developed in five sequential steps: Staff training, Patient recruitment, Patient admission, Patient reception and Patient care. Reasons for admission were categorized in urgencies and priority dental treatment. Results: The most prevalent reasons for consultation were prosthesis mismatch (18.37%), dental pain (16.33%) and fractured teeth (14.29%). In urgencies by need for treatment: due to infection or pain (24.44%) or to avoid pulp involvement (26.67%). The rest of the care did not require immediate attention. Regarding the OHIP-14Sp survey prior to care, in which patients were consulted for problems with their teeth, mouth or prosthesis, two questions were answered per dimension, for each dimension the following values were obtained: functional limitation (71.30% and 50.44%), physical pain (68.97% and 70.18%), psychological discomfort (75.00% and 74.14%), physical disability (57.39% and 46.09%), psychological disability (37.72% and 53.91%), social disability (33.91% and 30.97%) and handicap (27.83% and 25.86%). Conclusion: A teledentistry protocol for urgent and priority dental care of the elderly in the context of the COVID-19 pandemic with a focus on a general dentist remotely supported specialists was a useful tool to effectively systematize the care of elderly patients, reducing risk of exposure to COVID-19 and solving dental urgencies in this population